Control of pico‐hydro‐PV‐based distributed generation with battery support for off‐grid electrification. Issue 1 (14th September 2021) - Chandran, Vineet P.; Singh, Bhim
Abstract: This work presents the operation and control of a pico‐hydro‐solar photovoltaic (PV)‐battery energy storage (BES)‐based isolated renewable energy system (RES) feeding 3‐phase 4‐wire loads. For voltage regulation, to maintain frequency, and power quality improvement in this system, a 4‐leg VSC is used. The BES is connected to the DC‐link of the voltage source converter (VSC) through a bidirectional converter (BDC), which regulates the DC‐link voltage and controls the charging and discharging current of the battery. An advanced perturb and observe (AP&O)‐based MPPT control technique with drift free operation and capability to operate in the derated mode is adapted in this work. The VSC connected to PCC, injects or absorbs power from this system based on the difference of power between generation and the load. The modified complex co‐efficient filter (MCCF)‐based control technique monitors the power quality of this RES system and 4 leg VSC provides the source neutral current compensation. This control algorithm is used to extract the amplitude of the fundamental load current component with improved dynamic response, DC offset elimination and higher order harmonics removal capability. The ability of the presented control strategy for power quality improvement, power management, load balancing and neutral current compensation is reported in this work.